2019
DOI: 10.3390/coatings9090545
|View full text |Cite
|
Sign up to set email alerts
|

Washing Durability and Photo-Stability of NanoTiO2-SiO2 Coatings Exhausted onto Cotton and Cotton/Polyester Fabrics

Abstract: The purpose of this study was to assess and compare the durability of TiO2-SiO2 coatings applied in three concentrations onto two lightweight cellulose-based fabrics diverse in the composition against two external factors, repeated washings and prolonged intensive UV irradiation, by observing the changes in surface morphology, investigation of optical properties, and identification of specific molecular vibrations. The scanning electron microscopy (SEM) micrographs, diffuse reflectance spectroscopy (DRS) profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The ratio of nano-TiO2 used in cotton textile products varied between 0.2%-0.4% 63 and it was used between 3% - 9% by weight in another study. 64 Chitosan alone in providing flame retardancy to the fabric was sufficient. This is an important result in terms of reducing the use of chemicals in textile products.…”
Section: Analysis Results Of Chitosan-coated Fabricsmentioning
confidence: 97%
“…The ratio of nano-TiO2 used in cotton textile products varied between 0.2%-0.4% 63 and it was used between 3% - 9% by weight in another study. 64 Chitosan alone in providing flame retardancy to the fabric was sufficient. This is an important result in terms of reducing the use of chemicals in textile products.…”
Section: Analysis Results Of Chitosan-coated Fabricsmentioning
confidence: 97%
“…Moreover, a slight spectral difference occurs between 1300 and 1000 cm −1 for all final leather samples by increasing in intensity and widening of band at around 1080 cm −1 that may be attributed to Si–O–Si stretching vibration from the SiO 2 structural network. The band centered at 550 cm −1 is due to O–Ti–O vibrations from the TiO 2 network [ 61 ]. By comparing the spectral parameters of Exp 1-LH…Exp 4-LH (with plasma treatment) and Exp 5-LH and Exp 6-LH (without plasma treatment), it can be shown that the triple-helix conformation of collagen is not destroyed under cold plasma effect [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reflectance of cotton samples (Figure 2) is almost overlapped in the entire UV-Vis region, implying no superior UV-rays blocking properties and absorption to the visible light of the nanopowder-coated cotton samples (Chaudhari et al, 2012;Ojstršek and Fakin, 2019), probably due to the penetration of these nanoparticles into the cotton fabric material. All cotton samples show high reflectance values (>75%) across the full visible spectrum, in accordance with their white-light grey color.…”
Section: Results and Discusionsmentioning
confidence: 99%